Encefalinase de encefalo humano: purificação e caracterização - Duarte, Gloria Isolina Boente Pinto (1984)
The enzyme which hydrolysis enkephalin was isolated from human brain supernatant and purified about 2084 fold. The purified enzyme was homogeneous on the basis on the polyacryla mide gel electrophoresis, SDS polyacrylamide gel electrophore- sis and isoelectric focusing in sephadex G-25. The isolated enzyme cleaves only the Tyr-^-Gly2 bond of the enkephalin. So- dium dodecyl sulphate gel electrophoresis and sephadex G-200 chromatography indicated a single polypeptide chain with molecular weight of 100 000 daltons. The isoeletric focusing sho- wed that the purified enzyme has a pi near 4,9. The enzyme was activated by adittion of dithiothreitol and inhibited by Cu+' , 4-4- 4-4- 4-4- Zn , Mn , Ni , puromycin, bacitracin and p-aminomercuryace- tate but not was affected by EDTA. The K value for Met-enke - -5 phalin was 4,16 x 10 M suggesting that these enzyme may be enveloped in mechanisms of physiological hydrolysis of opioid peptides.